Can whole-body diffusion-weighted magnetic resonance sequence replace 18F-fluorodeoxyglucose-positron emission tomography in the management of lymphoma? - Rafik M. Ibrahim; Mwanajaa Abdalla Mwachui; Ahmed El-Gowily; Azza Mohamed Amin Darwish (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Positron emission tomography with 18F-fluorodeoxyglucose (18F-FDG-PET/CT) is the gold standard for staging and treatment response assessment in patients with malignant lymphoma. However, 18F-FDG-PET/CT uses significant dose of ionizing radiation, which is a potential risk of secondary malignancies. Whole-body diffusion-weighted MRI (WB-DW-MRI) is a promising, radiation-free alternative for staging and assessment of response in patients with lymphoma. However, till now, WB-MRI is not routinely used in patients with lymphoma. The aim of this study was to assess the role of whole-body diffusion-weighted MR sequence in management of lymphoma, compared to conventional FDG-PET CT, as well as to ascertain whether WB-DW-MRI is a good alternative to FDG PET/ CT for the diagnosis of lymphoma and subsequent treatment evaluation. The study was conducted on 20 patients (17males, 3 females) who presented with histopathologically proved lymphoma for initial evaluation or for follow-up. All patients were subjected to full history taking, clinical examination report review, as well as other imaging modalities whenever available, followed by FDG PET/CT examination. Patients were then further reevaluated by whole-body diffusion-weighted imaging to determine whether they were comparable in the diagnostic and or treatment response assessment. Results Thirty-six of our patients had non-Hodgkin’s lymphoma (NHL), while 4 had Hodgkin’s lymphoma (HL). Whole-Body DW-MRI and FDG PET/CT results assessment was done. Comparison between WB-DWI and FDG PET/CT revealed moderate agreement (κ = 0.573) for nodal regions and very good agreement (κ = 0.835) for extra-nodal regions. Finally, individual nodal regions varied from moderate to very good at a kappa value of > 0.69; with the exception of mediastinal hilar nodes which were fair (κ = 0.348). Conclusion WB-DWI demonstrates potential as a radiation-free alternative to PET/CT for staging and treatment response assessment in lymphoma patients. However, larger multicenter studies are still needed to validate WB-DW-MRI's diagnostic performance across diverse lymphoma subtypes.